Delayed leaf green-up is associated with fine particulate air pollution in China - Wendi Qu; Hao Hua; Ting Yang; Constantin M. Zohner; Josep Peñuelas; Jing Wei; Le Yu; Chaoyang Wu (Nature Communications)
Abstract Climate warming has led to earlier leaf green-up dates (GUD) with a greening trend of land surfaces in spring, yet the influence of multi-source particle pollution is not well understood. Using ground records and satellite observations of green-up date and fine particulate matter below 2.5 μm (PM2.5) over the last two decades in China, here we show that PM2.5 pollution is associated with reduced plant carbon uptake and delayed green-up dates. These effects offset climate-driven spring greening and reduce subsequent photosynthesis in China. We find that pollution-associated delays in green-up date are primarily linked to increased chilling demands and higher heat requirements. PM2.5-associated decreases in photosynthetically active radiation and maximum rate of carboxylation could also weaken plant photosynthetic capacity. Finally, when we incorporate a PM2.5 effect, phenological models predict up to a one-week delay in green-up date by the year 2060 compared to previous predictions. Negative feedbacks between anthropogenic pollution and terrestrial carbon uptake suggest unexpected uncertainty of China’s carbon neutral targets resulting from air pollution, with far-reaching implications for both ecosystem health and policy-making.